2022
DOI: 10.3390/ijms232012523
|View full text |Cite
|
Sign up to set email alerts
|

Global Proteomic Profile of Aluminum-Induced Hippocampal Impairments in Rats: Are Low Doses of Aluminum Really Safe?

Abstract: Hippocampus is the brain area where aluminum (Al) accumulates in abundance and is widely associated with learning and memory. In the present study, we evaluate behavioral, tissue, and proteomic changes in the hippocampus of Wistar rats caused by exposure to doses that mimic human consumption of aluminum chloride (AlCl3) in urban areas. For this, male Wistar rats were divided into two groups: Control (distilled water) and AlCl3 (8.3 mg/kg/day), both groups were exposed orally for 60 days. After the Al exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 90 publications
2
3
0
Order By: Relevance
“…The histological observations show atrophy and vacuolated astrocytes in the hippocampus of rats treated with aluminium only. This is in agreement with Bittencourt and colleagues in a report that aluminium causes hippocampal neurodegeneration and atrophy (Bittencourt et al, 2022). Hippocampal neurodegeneration and atrophy are reported to cause learning and memory deficits (Anand and Dhikav, 2012;Gemmell et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…The histological observations show atrophy and vacuolated astrocytes in the hippocampus of rats treated with aluminium only. This is in agreement with Bittencourt and colleagues in a report that aluminium causes hippocampal neurodegeneration and atrophy (Bittencourt et al, 2022). Hippocampal neurodegeneration and atrophy are reported to cause learning and memory deficits (Anand and Dhikav, 2012;Gemmell et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Histological analyses reveal that AlCl 3 mediates progressive alterations characterized by disorganization in the pyramidal cellular arrangement and a decrease in neuronal density in the CA3 hippocampal area as compared with the control group, which correlated with the biochemical changes revealed in this work. These ndings were correlated to those claimed by Bittencourt et al, ; Fernandes et al, and Maya et al, [24,32,41] These neurotoxic effects of Al may be justi ed by the tropism that this metal has for CNS structures and cause oxidative damage to hippocampal cells.…”
Section: Discussionsupporting
confidence: 85%
“…We selected the CA3 area for light microscopic analyses at magni cations of ×20. After, the photomicrographs were taken and analyzed using ImageJ software [23,24].…”
Section: Histological Analysismentioning
confidence: 99%
“…We have used SHK in our study to treat the rats for experimentally induced AD using AlCl 3. As stated earlier, it is well known that AlCl 3 is a neurotoxicant to brain cells like neurons, astrocytes, glial cells, and vascular cells in both in vivo and in vitro experimental conditions (Bittencourt et al, 2022; Yang et al, 2019) and was also reported to be present in brain tissues of age-related dementia and Alzheimer’s patients (Exley & Clarkson, 2020).…”
Section: Discussionmentioning
confidence: 81%